Detection of interleukin-lb and tumor necrosis factor (TNF-a) in macrophages treated with recombinant bcg (rBCG) expressing the 19kDa c-terminus of the merozoite surface protein (MSP-lC) - Mohd Abdul Halim, Abd Latif (Universiti Sains Malaysia, 2009)
Malaria remains a serious public health problem and ·causes an ·estimated 2 million ·deaths worldwide each year. The increase of drug resistant parasites and insecticide resistant mosquito vectors in certain areas worsens the situation especially against P. falciparum. As such, production ·of vaccine is very important in malaria prevention. In this study, a recombinant Mycobacterium bovis bacille Calmette-Guerin (rBCG) which expressed the 19kDa C-terminus of the merozoite surface protein (MSP-1 C) was developed against the blood stage of malaria infection. The inflammatory cytokines ·such as interleukin-1f!(1l-1~) and tumor necrosis factor-a (TNF-a) produced by macrophages are important for elimination of malaria infection. The ability of our rBCG construct to stimulate the production ·of pro-inflammatory cytokines by macrophages was determined at ·different incubation times (24 hours, 72 hours and 120 hours) and different concentrations (1:20 and 1:40 (macrophage: BCG or rBCG)). This study showed that the production of IL-1P and TNF--a was -significantly higher in macrophages treated with rBCO compared to BCG, which could be observed at all incubation times and concentrations performed. This rBCG construct is able to stimulate the production of cytokine and perhaps preventing malaria infection especially at the blood stage.